(untitled) (Colombia Medica, 2006)
Objective: The aim of the study was to describe the prevalence of Helicobacter pylori and psychosocial stress in patients with chronic gastritis. Methods: A pilot case-control study was performed in patients with chronic gastritis. The study group included patients infected with H. pylori and the control group included patients without infection. The patients were recruited at the Valle University Hospital (VUH) and the Valle del Lili Foundation (VLF) in Cali, Colombia during 2003. The H. pylori infection was determined by gastric endoscopy and the psychosocial stress by the Hospital Anxiety Depression Scale (HADS). Results: 164 patients were included, 74 (45.1%) in VUH and 90 (54.9%) in VLF. The socio-demographic characteristics were comparable in both institutions and both groups. H. pylori infection was observed in 113 (68.9%) patients and psychosocial stress in 115 (70.1%). Anxiety levels were higher than depression levels; (anxiety median=9, range 1-20; depression median=6, range 0-17) especially in VUH (p=0.03) associated to low socioeconomic status (p< 0.01). The psychosocial stress was not associated with H. pylori infection (p=0.69). Conclusion: Patients with chronic gastritis had a high prevalence of H. pylori infection and psychosocial stress without association between the two variables.